Analisis Bauran Promosi Terhadap Keputusan Pembelian Pada Pusat Oleh-Oleh Khas Jambi (Studi Kasus Outlet Temphoyac) - Riko Mappadeceng; Muhammad Amali (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This research aims to identify marketing mix factors and find out the current promotional strategy of Temphoyac Outlets, Identify influential factors in, develop a Temphoyac Outlet promotion strategy and Analyze more appropriate promotional strategies for Temphoyac Outlets and provide appropriate alternative recommendations for Temphoyac Outlets. This research activity is limited by the field of promotion. This research looks at the company's side, how the company executes its promotional strategy, and discusses the selection of the most effective promotional programs that can be considered based on the factors that influence the selection of promotional programs that can be found from interview results and questionnaires. The respondents selected are parties involved in the promotion activities of Temphoyac Outlets and consumers in Temphoyac Outlets, This study was analyzed using multiple linear regressions.with results Y = 6,906 + 0.515 , marketing mix factors consisting of product quality, promotion and distribution channels, each had a significant positive influence, and together had a positive and significant influence on the purchasing behavior of a product/item.